Branding Strategy to Increase Sales of Products from Palm Trees in the Bojong Hamlet, Sukabumi Regency - Amanna Dzikrillah Lazuardini; Salix Fini Maris (Eastasouth Institute, 2022)
Ant sugar is processed from sap which has a longer process than palm sugar. Ant sugar itself is one of the preparations from the palm plant which is processed by residents of Bojong Hamlet, Cicadas Village, which is used as a livelihood for residents for their daily needs. The existence and position of these products are still not competitive, they are not well known and their sales are very minimal. On the other hand, Bojong hamlet residents also experience difficulties in producing, innovating and marketing properly. The purpose of this research is to make raw material products, product innovation and product sales in local and international markets, so that products in Bojong Hamlet can increase and be able to compete with other similar products in the market. The method used in this program is to provide education to sugar palm farmers about the uniqueness of packaging, taste innovation and making attractive packaging and marketing. While conducting the education, the results were obtained, namely the interest of the people of Bojong Hamlet, Cicadas Village, to innovate in product development, packaging innovation and attractive sales.